2016
DOI: 10.1097/qai.0000000000000970
|View full text |Cite
|
Sign up to set email alerts
|

Empiric TB Treatment of Severely Ill Patients With HIV and Presumed Pulmonary TB Improves Survival

Abstract: Rationale In 2007, WHO issued emergency recommendations on empiric treatment of sputum acid-fast bacillus (AFB) smear-negative patients with possible tuberculosis (TB) in HIV-prevalent areas, and called for operational research to evaluate their effectiveness. We sought to determine if early, empiric TB treatment of possible TB patients with abnormal chest radiography or severe illness as suggested by the 2007 WHO guidelines is associated with improved survival. Methods We prospectively enrolled consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…First, clinician attitudes in urban settings and thresholds for empiric TB treatment initiation in patients with low CD4 changed during the course of our clinical trial. 27 These treatment decisions were likely driven by data from SSA showing TB as a key cause of mortality after ART initiation 2,4,28 and high rates of prevalent TB in patients initiating ART in a high-burden setting. In this study, 6.5% of the screened patients had smear-positive TB before ART, slightly lower than previously reported rates of prevalent TB in HIV-infected patients in SSA (15-25% in South Africa 29,30 and 10-15% for other sub-Saharan African countries 23,31 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, clinician attitudes in urban settings and thresholds for empiric TB treatment initiation in patients with low CD4 changed during the course of our clinical trial. 27 These treatment decisions were likely driven by data from SSA showing TB as a key cause of mortality after ART initiation 2,4,28 and high rates of prevalent TB in patients initiating ART in a high-burden setting. In this study, 6.5% of the screened patients had smear-positive TB before ART, slightly lower than previously reported rates of prevalent TB in HIV-infected patients in SSA (15-25% in South Africa 29,30 and 10-15% for other sub-Saharan African countries 23,31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Developing a strong evidence base for predictors of poor outcomes in seriously ill inpatients could result in improved treatment and diagnostic algorithms. Empiric antituberculosis treatment improved 8-week survival of inpatients with WHO danger signs and negative sputum smears, but had no effect on survival in inpatients without danger signs in a Ugandan study; [ 4 ] which indicates that the danger signs have prognostic value.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of association between post-XP empirical treatment or microbiologically confirmed treatment and the risk of death was also found by three recent studies among both ambulant and hospitalized ART naïve patients [18, 28–30]. However, a recent systematic review on the impact of tuberculosis nucleic amplification tests, such as Xpert® MTB/RIF, concluded that the evidence has been of limited scientific rigour and from a relatively small number of settings, limiting its validity and generalisability [13].…”
Section: Discussionmentioning
confidence: 55%